Risk factors of hyperbilirubinemia in neonates: A case control study - Selvam, Sinduja; Taksande, Amar (International Journal of Psychosocial Rehabilitation, 2020)
Jaundice is the most frequent reason in neonates, requiring medical intervention and admission. It is often a normal condition in the neonates, but when the levels of the bilirubin exceed a certain range, it requires intervention because it can and can have serious neurological sequelae and may even cause death in those who survive. Therefore earlier recognition and appropriate intervention is required, in order to prevent complications like severe hyperbilirubinemia, acute encephalopathy and kernicterus. There are some factors which can put the baby at an increased risk of developing hyperbilirubinemia. These risk factors may be maternal or neonatal. Maternal risk factors can include any history of drugs, other co-morbid conditions, ABO, Rh incompatibility, ethnicity and others. Neonatal risk factors include gestational age, gender, infections, trauma during birth, etc. In this study, we have attempted to study the various risk factors of neonatal hyperbilirubinemia. The objective is to determine the various foetal and maternal risk factors associated with neonatal jaundice and to identify the modifiable factors, so the early recognition and follow of neonates at risk can help reduce the incidence of jaundice and its sequale.